The good neighbor : a novel - Nathan, Amy Sue (St. Martin's Griffin, 2015)
"Izzy Lane never thought of herself as a liar. In fact, she's always played by the rules. She's an excellent mother, has loyal friends, and a rich career as a school counselor. Fresh from a new divorce, however, Izzy feels like she needs a little fun. So when, on a whim, she starts a blog it seems like a rather benign indulgence. But as her online quips begin to gain traction, Izzy makes a slip. Somehow a new boyfriend winds his way into the picture. The problem? Izzy makes him up. What, at first, feels like a harmless fib quickly spins out of control and Izzy must figure out how to balance fantasy and reality. Keeping up appearances while managing an absent ex-husband, two very nosy friends, a toddler son, and full-time job soon prove impossible, and Izzy feels utterly lost. It's only when her long-time neighbor and surrogate mother, Mrs. Feldman, re-enters her life that Izzy begins to see the mess she's made. And it's with Mrs. Feldman's guidance that Izzy learns to face reality, find comfort in new norms, and open herself up to the possibility of real love. "--